Mapping aid effectiveness and gender equality : global findings and key messages - Chiwara, Letty (UNIFEM New YorkUS, 2008)
Provides an overview of the issues and trends that emerged from mapping studies on aid effectiveness, gender equality and women's empowerment in 12 countries.